Photosynthetic and anatomical responses of Eucalyptus grandis leaves to potassium and sodium supply in a field experiment - Battie-Laclau, Patricia; Laclau, Jean-Paul; Beri, Constance; Mietton, Lauriane; Muniz, Marta R Almeida; Arenque, Bruna Cersózimo; Piccolo, Marisa de Cassia; Jordan-Meille, Lionel; Bouillet, Jean-Pierre; Nouvellon, Yann (Wiley, 2013)
Although vast areas in tropical regions have weathered soils with low potassium (K) levels, little is known about the effects of K supply on the photosynthetic physiology of trees. This study assessed the effects of K and sodium (Na) supply on the diffusional and biochemical limitations to photosynthesis in Eucalyptus grandis leaves. A field experiment comparing treatments receiving K (+K) or Na (+Na) with a control treatment (C) was set up in a K-deficient soil. The net CO2 assimilation rates were twice as high in +K and 1.6 times higher in +Na than in the C as a result of lower stomatal and mesophyll resistance to CO2 diffusion and higher photosynthetic capacity. The starch content was higher and soluble sugar was lower in +K than in C and +Na, suggesting that K starvation disturbed carbon storage and transport. The specific leaf area, leaf thickness, parenchyma thickness, stomatal size and intercellular air spaces increased in +K and +Na compared to C. Nitrogen and chlorophyll concentrations were also higher in +K and +Na than in C. These results suggest a strong relationship between the K and Na supply to E. grandis trees and the functional and structural limitations to CO2 assimilation rates. © 2013 John Wiley & Sons Ltd.
Keywords: A-Ci curves; Eucalypt; K; Leaf anatomy; Mesophyll conductance; Na; Nutrient; Photosynthesis; Stomatal conductance